Growth, gas exchange and competitive ability of Sorghum halepense populations under different soil water availability - Leguizamón, Eduardo S. (2011)
Different studies have determined that environmental variation is a key factor determining the outcome of competition within plant communities. Considering the importance of the resource water in non-irrigated lands of Argentina, the aim was to determine the effects of water deficit on relative growth rate (RGR), root length ratio (RLR), gas exchange and competitive ability of Sorghum halepense populations collected in humid and subhumid regions of the Pampa plains. Under semi-controlled conditions, we compared plants of seven S. halepense populations subjected to three different levels of soil water availability during 3 wk: Field capacity (FC), 75% FC and drought (D). Moreover, total above-ground biomass of S. halepense and Zea mays plants growing together in competition was determined. It was found that those plants collected in humid or subhumid regions had greater RGR, gas exchange and RLR under FC and D, respectively. Zea mays achieved a higher competitive ability than S. halepense under FC, but plants collected in humid regions outcompeted the crop when grown at 75% FC. Sorghum halepense plants collected in subhumid regions dominated under D. Root length ratio may have favored the maintenance of high levels of gas exchange and also high RGR, thus contributing to sustain a competitive hierarchy under soil water stress.